Investigation of the Anti-cataract and Antioxidant Activities of Cnidoscolus aconitifolius Leaves Extract In vitro - Bulama, Henry; Dahiru, Daniel; Madu, Joshua (Iraqi Journal of Science, 2021)
Background: Cataract is a major cause of visual impairment and blindness around the world. This study evaluated the in vitro antioxidant and anti-cataract activities of Cnidoscolus aconitifolius leaves extract and fractions. Antioxidant activities were evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azinobis (3-ethylbenzothiozoline-6-sulfonic acid) (ABTS), total reducing power, and hydrogen peroxide scavenging assays. Anti-cataract potential was evaluated in vitro using goat lenses divided into eight groups of different treatments and incubated in artificial aqueous humor at 37 °C for 72 hours. Glucose-induced opacity in the lenses was observed and biochemical indices quantified (catalase, Malondialdehyde (MDA) and total protein in the lens homogenate).Results: The crude extract and its fractions possess substantial antioxidant activities. The aqueous fraction exhibited the best DPPH radical scavenging activity (IC50 value 78.599 µg/ml); while the dichloromethane fraction exhibited the highest ABTS radical scavenging activity with IC50 66.68 µg/ml. The anti-cataract evaluation of crude and fractions at 250 μg/ml showed a significant increase (p<0.05) in the total protein and catalase activity compared to the cataract control group. The malonaldehyde level decreased significantly (p<0.05) in all the treated groups.